Academic Referencing on University Library Websites: A Call for Clear, Coherent and Correct Categorisation. Issue 1 (2nd January 2017) - Trevethan, Robert; Betta, Michela
Abstract: Although commendable in many respects, some university library websites categorise academic referencing styles and systems in ways that are unhelpful and inaccurate. In this article, the four major styles of referencing (Harvard, Oxford, Vancouver and Modern Language Association) are described in sufficient detail to demonstrate that they should be clearly differentiated from each other. Where appropriate, systems that fall within these styles are also described to illustrate that they should be grouped according to the style within which they belong but should also be clearly demarcated. As a result of this, recommendations are made that university library websites provide clearer and more coherent, complete and accurate information about referencing.